Respuesta :

Answer: 1

Step-by-step explanation:

Method #1: Using the log rules (+ → x and - → ÷)

  log₂4 + log₂16 - log₂32

= log₂[tex](\frac{4*16}{32})[/tex]

= log₂[tex](\frac{64}{32})[/tex]

= log₂2

= 1

Method #2: Using log rules to simplify each expression

log₂4 = x              log₂16 = x                  log₂32 = x

      4 = 2ˣ                    16 = 2ˣ                       32 = 2ˣ

      2² = 2ˣ                   2⁴ = 2ˣ                       2⁵ = 2ˣ

        2 = x                      4 = x                          5 = x

log₂4 = 2               log₂16 = 4                 log₂32 = 5

             2     +                      4       -                        5     =     1